Potential distribution prediction of Deyeuxia angustifolia in the Tumen River Basin and analysis of major impact factors - Zong, Jin; Cao, Guanglan; Jin, Xuemei; Jin, Ri; Zhu, Weihong (Frontiers in Environmental Science, 2022)
Deyeuxia angustifolia acts as an indicator of the changes in wetland ecosystems and plays an important ecological role in their functions. Previous studies have shown that the Tumen River Basin is of wide global interest as a transboundary basin area with abundant wetland ecological resources. Despite the implementation of wetland conservation measures in recent years, the distribution area of D. angustifolia in this basin has been reduced due to climate change and anthropogenic activities. Therefore, we used MaxEnt and geographic information system to model a suitable habitat for this species, simulated changes in the habitat, and applied Jackknife to assess the influencing environmental variables. The Jackknife tests showed that slope orientation, solar radiation in September, and total nitrogen were the dominant environmental factors affecting the potential distribution of D. angustifolia. Compared to the current distribution, the total area of land highly and moderately suitable for this species will decrease in the 2050’s and 2070’s, respectively, under two representative concentration paths (RCPs), shifting the centroid of its suitable area and direction of wetland degradation to the northeast. Our study of the projected potential distribution of D. angustifolia in the basin under future climate change could provide important information for its conservation, management, sustainable use, and early warning to prevent its extinction.